Antidiabetic potential of the ethyl acetate extract of Physalis alkekengi and chemical constituents identified by HPLC-ESI-QTOF-MS. (28th October 2018) - Zhang, Qiang; Hu, Xiao-Fang; Xin, Man-man; Liu, Hong-Bing; Sun, Li-Juan; Morris-Natschke, Susan L.; Chen, Yong; Lee, Kuo-Hsiung
Abstract: Ethnopharmacological relevance: The edible plant Physalis alkekengi (PA) is used in traditional medicine to treat diabetes. However, the anti-diabetic effects and constituents of the fruit and aerial parts of this plant have not been studied extensively. Aim of the study: The purpose of this study was to investigate the antidiabetic potential of Physalis alkekengi and identify its chemical constituents. Materials and methods: In the present study, the in vitro glucose uptake capacity was tested using the 2-[ N -(7-nitrobenz-2-oxa-1, 3-diazol-4-yl)amino]-2-deoxy-d -glucose (2-NBDG) assay in HepG2 cells. Secondly, the anti-diabetes effects of the ethyl acetate extracts of the aerial parts/fruit (EAP/EAF) of P. alkekengi were evaluated in high-fat diet-fed and streptozotocin-induced diabetic rats (seven groups, n = 7) daily at doses of 300 and 600 mg/kg for 28 days. Fasting blood glucose (FBG) was measured with a glucometer and the levels of total cholesterol (TC), triglyceride (TG), glycated serum protein (GSP), and fasting insulin (FINS) were measured by ELISA. Furthermore, insulin sensitivity index (ISI) and homeostasis model assessment-insulin resistance index (HOMA-IR) were calculated based on FBG and FINS. Changes in blood glucose concentration were assessed after an oral glucose challenge in diabetic rats treated with EAF and EAP extracts. In all assays, rosiglitazone, a current antidiabetic drug and insulin sensitizer, was also tested. Finally, the compounds in EAP were identified by HPLC-ESI-QTOF-MS analysis. Results: EAP increased the uptake of 2-NBDG, a measure of direct glucose uptake, in HepG2 cells. Next, in diabetic rats treated with P. alkegenki extracts for 28 days, the levels of FBG, TC, TG and GSP and were lowered effectively, while FINS was increased significantly. EAP/EAF enhanced insulin sensitivity significantly as measured by ISI and HOMA-IR along with oral glucose tolerance test analysis. The EAP generally exerted the greatest effects. Lastly, a HPLC-ESI-Q-TOF-MS analysis identified 50 compounds, including 26 physalins, 10 flavonoids, and 9 phenolic acids, with 21 compounds found for the first time in P. alkekengi . Conclusions: The results support the merit of P. alkekengi as an antidiabetic herbal medicine or dietary supplement. Graphical abstract: